2021
DOI: 10.1136/oemed-2021-107427
|View full text |Cite
|
Sign up to set email alerts
|

Boosting positive mood in medical and emergency personnel during the COVID-19 pandemic: preliminary evidence of efficacy, feasibility and acceptability of a novel online ambulatory intervention

Abstract: ObjectivesThe aim of this project was to test the efficacy of a brief and novel online ambulatory intervention aimed at supporting psychological health and well-being for medical personnel and first responders during the COVID-19 pandemic.MethodsInterested participants, n=28, actively employed as medical personnel, support staff and emergency responders, in the Midwestern USA in May–June of 2020, provided informed consent and were randomised to complete either low-dose or high-dose intervention, one time daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 12 publications
1
42
1
Order By: Relevance
“…Given its comprehensiveness, the PROSPER framework may be particularly relevant during the COVID-19 pandemic; for example, a recent investigation ( Lee et al, 2022 ) has demonstrated that a 4-session PROSPER-based psychological intervention program enhanced positive relationships with peers among pre-service teachers in Hong Kong during the COVID-19 pandemic. There is also research showing how its dimensions, such as positive emotions ( Coifman et al, 2021 ), relationships ( Hutchinson et al, 2021 ), perceived competence ( Behzadnia & FatahModares, 2020 ), resilience ( Pink et al, 2021 ), strengths ( Datu, Yuen, et al, 2022 ; Datu, Valdez, et al, 2022 ), engagement ( Ployhart et al, 2021 ), and meaning in life ( Newman et al, 2021 ), operate as either protective psychological resources or key psychological outcomes during the pandemic. Furthermore, the present research organized well-being outcomes into two broad categories, namely intrapersonal and interpersonal dimensions, given that previous literature ( Ryff, 1995 ) has offered a more nuanced approach in understanding the role of PWB's dimensions in different cultural contexts.…”
Section: Prosper Frameworkmentioning
confidence: 99%
“…Given its comprehensiveness, the PROSPER framework may be particularly relevant during the COVID-19 pandemic; for example, a recent investigation ( Lee et al, 2022 ) has demonstrated that a 4-session PROSPER-based psychological intervention program enhanced positive relationships with peers among pre-service teachers in Hong Kong during the COVID-19 pandemic. There is also research showing how its dimensions, such as positive emotions ( Coifman et al, 2021 ), relationships ( Hutchinson et al, 2021 ), perceived competence ( Behzadnia & FatahModares, 2020 ), resilience ( Pink et al, 2021 ), strengths ( Datu, Yuen, et al, 2022 ; Datu, Valdez, et al, 2022 ), engagement ( Ployhart et al, 2021 ), and meaning in life ( Newman et al, 2021 ), operate as either protective psychological resources or key psychological outcomes during the pandemic. Furthermore, the present research organized well-being outcomes into two broad categories, namely intrapersonal and interpersonal dimensions, given that previous literature ( Ryff, 1995 ) has offered a more nuanced approach in understanding the role of PWB's dimensions in different cultural contexts.…”
Section: Prosper Frameworkmentioning
confidence: 99%
“…The study durations ranged from 1 week to 15 months; one study did not report this information [ 47 ]. Studies were conducted across a variety of international settings; 4 were conducted in the United States [ 48 - 50 ], whereas the remainder were conducted in Iran [ 47 ], Germany [ 51 ], Australia [ 52 ], and the Netherlands [ 53 ]. Study participants included a range of health care professional disciplines (n=1573), and studies were carried out in academic university settings [ 49 , 50 , 54 ] or on study programs within health care settings [ 48 , 51 - 53 ]; one study did not provide this information [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted across a variety of international settings; 4 were conducted in the United States [ 48 - 50 ], whereas the remainder were conducted in Iran [ 47 ], Germany [ 51 ], Australia [ 52 ], and the Netherlands [ 53 ]. Study participants included a range of health care professional disciplines (n=1573), and studies were carried out in academic university settings [ 49 , 50 , 54 ] or on study programs within health care settings [ 48 , 51 - 53 ]; one study did not provide this information [ 47 ]. Of the 4 health care settings, 1 (25%) study was conducted in a rural primary care setting [ 52 ], 1 (25%) was conducted in hospital and ambulance departments [ 51 ], 1 (25%) was conducted across 2 urban hospitals and police and fire departments [ 48 ], and 1 (25%) was conducted across a variety of health care institutions [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations